Creating a Safe and Inclusive School Culture: Anti-Bullying Program Implementation in a Faith-Based Primary School - Jayangti, Jayangti; Kamal, Helmi; Masri, Subekti (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
Bullying remains a persistent issue in primary education, requiring context-sensitive and value-driven interventions, especially in culturally and religiously grounded school environments. This study explores the implementation of an anti-bullying education program at SD Darud Da’wah War-Irsyad II (DDI II) Palopo, a faith-based Islamic elementary school in Indonesia, to understand its structure, processes, and challenges. Employing a qualitative descriptive design, data were collected through in-depth interviews, school observations, and document analysis. The participants included school leaders, Islamic education teachers, and homeroom teachers directly involved in the program's development and execution. The findings revealed that the program was structured across daily, weekly, and annual activities, all of which were infused with Islamic values such as rahmah (compassion), ukhuwah (brotherhood), and adl (justice). Its implementation involved stages of awareness-building, task force coordination, curriculum integration, peer support systems, and parental involvement. Challenges included students' limited awareness of non-physical bullying, teachers’ lack of training in handling psychological aggression, underreporting due to social stigma, and the absence of a formal evaluation mechanism. This study contributes to the field by offering a practical and culturally embedded model for anti-bullying education rooted in religious ethics. The model is scalable, cost-effective, and adaptable for other faith-based schools, making it relevant for educators and policymakers seeking sustainable approaches to school safety and character development in religious contexts.